Time to free our universities - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2020)
DOES “education” in Malaysia need a “new” normal? Or are we being dragged once again by herd mentality? Here are five reasons why we should pause, rethink, and opt for a “renewed” normal. That is, to implement what we should have done a long time ago to avoid being in the predicament we are in today.